Reshaping of soil carbon and nitrogen contents in quincentenary ancient rice terraces: The role of both short-term abandonment and prokaryotic functional groups - Li, Wenqing; Li, Zhongwu; Liu, Yaojun; Nie, Xiaodong; Deng, Chuxiong; Zhang, Guangye; Wang, Shuyuan; Xiao, Tao; Zheng, Han (Frontiers in Microbiology, 2022)
Microbial communities and functions play an important role in soil carbon and nitrogen transformations, and, in recent decades, the abandonment of terraces is prevalant in the hilly areas of China. However, it is unclear how soil carbon and nitrogen contents and prokaryotic communities changed as a result of the abandonment of ancient rice terraces. Soil profiles ranging from 0 to 120 cm were excavated on drylands, forestlands (both converted due to the abandonment of ancient rice terraces), and ancient rice terraces. The FAPROTAX database was used to predict soil prokaryotic functional groups. The results showed that soil organic carbon (SOC) and total nitrogen (TN) contents of abandoned ancient rice terraces in drylands (51.09 and 33.20%) and forestlands (31.76 and 16.59%) were significantly reduced. Soil prokaryotic diversity and community composition changed dramatically after the abandonment of terraces and were mainly affected by soil pH and ammoniacal nitrogen (NH4+-N). Community composition was more similar in drylands and forestlands. Moreover, the abundance of transformation functional genes of carbon (57.01 and 50.80%) and nitrogen (15.25 and 22.36%) in bacterial communities was significantly reduced, and of carbon in the archaeal communities decreased sharply (28.10 and 46.50%), in drylands and forestlands. These findings indicate that short-term abandonment of ancient rice terraces reduces soil carbon and nitrogen contents, which may be closely related to the decline of prokaryotic functional groups. The prevalence of short-term abandonment of rice terraces in the hilly areas of China may pose adverse ecological risks.